PRADER-WILLI SYNDROME IDENTIFIED BY METHYLATION SPECIFIC MULTIPLEX LIGATION DEPENDENT PROBE AMPLIFICATION (MS-MLPA) - Simona Loredana Vasilache; Adelina Micheu; Claudia Banescu; Valeriu Moldovan; Carmen Duicu; Ionela Maria Pascanu; Oana Marginean (Amaltea Medical Publishing House, 2017)
Prader-Willi syndrome (PWS) is a multisystemic complex genetic disorder caused by lack of expression of genes on the paternally inherited chromosome 15q11.2-q13 region. There are three major genetic subtypes in PWS: paternal 15q11-q13 deletion (70% of cases), maternal uniparental disomy 15 (25-30%) and imprinting defect (1-3%).The clinicians confront the challenge of discern more clearly between the classic PWS and the various PWS-like syndrome (PWLS). It is necessary to study these issues at the molecular level to explain these genetic similarities and to provide appropriate genetic counseling and treatment. We present a case of a 6 years old male patient with severe hypotonia, feeding difficulties in neonatal period, developmental delay in neuromotor acquisition, hyperphagia and obesity (BMI: +4.66 SD).The genetic analysis methylation specific multiplex ligation dependent probe amplification (MS-MLPA) revealed an aberrant methylation of CpG island. It is important to mention that a precise diagnosis of PWS and an early multidisciplinary approach are essential for efficient long-term management, for preventing complications and improve quality of life in this patients.